Is Small Beautiful? Financial Structure, Size and Access to Finance - Beck, Thorsten; Demirgüç-Kunt, Asli; Singer, Dorothe (Elsevier, 2013)
Combining two unique data sets, this paper explores the relationship between financial structure and firms’ access to financial services. Specifically, it considers the importance of three different types of financial institutions: low-end financial institutions, specialized lenders, and banks. Two findings stand out. First, dominance of the financial system by banks is associated with lower use of financial services by firms of all sizes, while low-end financial institutions and specialized lenders seem particularly suited to ease access to finance in low-income countries. Second, there is no evidence that smaller institutions are better in providing access to finance.